The Influence of STEM (Science, Technology, Engineering, and Mathematics) Based Learning on Science and Science Learning Outcomes - Mailana, Aldi; Dafit, Febrina (Jurnal Penelitian Pendidikan IPA, 2023)
The teacher has not implemented the learning process using STEM (Science, Technology, Engineering, and Mathematics) optimally in the application of science subjects, and science learning outcomes for class IV elementary schools are generally not optimal. The research was conducted to find knowledge regarding whether there is an impact of using the STEM learning model on science learning outcomes in elementary schools. The type of approach used is quantitative with a research design using a quasi-experiment. Sampling in this study used purposive sampling, and because the population in this study was class IV students consisting of 4 classes, this review sample consisted of 2 classes, namely the control class and the experimental class. The sample for this research consisted of 40 students consisting of 20 students from class IVA and 20 students from class IV B. In this research, the data collection methods used were observation, interviews, and tests. Data analysis techniques use normality, homogeneity, and hypothesis tests, as well as descriptive analysis and test criteria. Based on data analysis of research findings, STEM-based learning has a significant positive impact on the performance of students in class IV science lessons and improving science learning outcomes